2023
DOI: 10.1088/1361-6501/acb6e3
|View full text |Cite
|
Sign up to set email alerts
|

3D ground penetrating radar cavity identification algorithm for urban roads using transfer learning

Abstract: 3D ground penetrating radar (GPR) is the main method for the detection of underground cavities in urban roads. The number of road cavity samples detected by 3D radar is small, whereas the intelligent identification model require a large number of learning samples for model training, resulting in inadequate model training. This causes the model to be less accurate in identifying cavities, resulting in many misses and misjudgments. Given the above problems, combined with the detection characteristics of the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…As a result, based on data processing, it can be concluded that GPR is a non-destructive, fast, and economical method for evaluating road structures [7]. Through various data acquisition and processing techniques, studies have shown significant success in using GPR to gather information for verifying the state and condition of materials [8,9]. This technology helps overcome the constraint of insufficient cavity samples for 3D radar detection on intelligent learning model training, reduces algorithm training costs, and improves identification accuracy [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, based on data processing, it can be concluded that GPR is a non-destructive, fast, and economical method for evaluating road structures [7]. Through various data acquisition and processing techniques, studies have shown significant success in using GPR to gather information for verifying the state and condition of materials [8,9]. This technology helps overcome the constraint of insufficient cavity samples for 3D radar detection on intelligent learning model training, reduces algorithm training costs, and improves identification accuracy [10,11].…”
Section: Resultsmentioning
confidence: 99%